PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS LINGKUNGAN HIDUP KABUPATEN MUSI RAWAS - Suyadi Suyadi; Azhar Azhar; Setiawan Setiawan (LPPM UNIVERSITAS BINA INSAN, 2018)
This study entitled The Effect of Motivation and Work Environment on Employee Performance at the Environmental Service Office of Musi Rawas Regency. The objectives to be achieved in this study are to find out the Effect of Motivation and Work Environment on Employee Performance at the Environmental Service Office of Musi Rawas Regency. The sample in this study were all employees who worked in the Environmental Office of Musi Rawas Regency, which numbered 51 people. Data collection techniques in this study used observation, documentation and questionnaires. The analysis technique uses simple regression analysis, correlation test, t test, multiple linear regression, determination test, and f test. Based on the analysis and discussion it can be concluded that 1) The Effect of Motivation on Employee Performance at the Environmental Service Office of Musi Rawas Regency, where the results of simple linear regression test Y = 56.430 + 0.492 Motivation, correlation coefficient value R = 0.434 and t-test tcount = 3,370> t table = 2,009. 2) The Effect of the Work Environment on Employee Performance at the Environmental Service Office of Musi Rawas Regency. where obtained the results of simple linear regression Y = 55.980 + 0.431 Work Environment, correlation coefficient value of R = 0.522 and t-test value of tcount = 4.288> t table = 2.009. 3) Effect of Motivation and Work Environment on Employee Performance at the Environmental Service Office of Musi Rawas Regency, where the results of multiple linear regression test Y = 41,828 + 0,318 X1 + 0,346 X2, determination coefficient value R2 = 0,584 and Fcount value obtained is 12,400> Ftable = ¬ 3,19